Involvement of glutamate in retinal protection against ischemia/reperfusion damage induced by post-conditioning. - Fernández, Diego Carlos (2009)
Retinal ischemia could provoke blindness and there is no effective treatment against retinal ischemic damage. Brief intermittent ischemia applied during the onset of reperfusion (i.e., postconditioning) protects the retina from ischemia/reperfusion injury. Multiple evidences support that glutamate is implicated in retinal ischemic damage. We investigated the involvement of glutamate clearance in postconditioning-induced protection. For this purpose, ischemia was induced by increasing intraocular pressure for 40 min, and 5 min after reperfusion, animals underwent 7 cycles of 1min/1min ischemia/reperfusion. One, 3, or 7 days after ischemia, animals were subjected to electroretinography and histological analysis. The functional and histological protection induced by postconditioning was evident at 7 (but not 1 or 3) days post-ischemia. An increase in Müller cell glial fibrillary acidic protein (GFAP) levels was observed at 1, 3, and 7 days after ischemia, whereas postconditioning reduced Müller cells GFAP levels at 3 and 7 days post-ischemia. Three days after ischemia, a significant decrease in glutamate uptake and glutamine synthetase activity was observed, whereas postconditioning reversed the effect of ischemia. The intravitreal injection of supraphysiological levels of glutamate mimicked electroretinographic and histological alterations provoked by ischemia, which were abrogated by postconditioning. These results support the involvement of glutamate in retinal protection against ischemia/reperfusion damage induced by postconditioning.